Discrete time signal processing - A Nagoor Kani (New Delhi CBS Publishers and Distributors Pvt Ltd, 2024)
his book is organized into 5 chapters. The basic concepts of discrete time signals and systems and the computation of DFT and FFT are presented in first chapter. One chapter is devoted to each topic in discrete time signal processing like IIR filters, FIR filters, finite word length effects and digital signal processors. Considering the highly mathematical nature of this subject, more emphasis has been given to problem-solving methodology. Each chapter provides the foundations and practical implications with a large number of solved numerical examples for better understanding. Salient Features Clear explanation of concepts with appropriate diagrams. Additional explanations for solutions and proofs are provided in separate boxes. Different types of fonts for text, proof and solved problems for better understanding. Step-by-step presentation of proofs and solved problems. Important concepts are summarized at the end of each chapter for quick reference. MATLAB programming will be useful for laboratory and other projects. TMS320 series DSP assembly language programs will be useful for laboratory and other projects. MATLAB programs related to this book are available free on CBSiCentral App.
Keywords: Discrete Fourier Transform; Infinite Impulse Response (IIR) Filters; Finite Impulse Response (FIR) Filters; Finite Word Length Effects; Digital Signal Processors; For Anna University; ECE Course